Pendampingan Mahasiswa PPL dalam Akselerasi Sinkronisasi Data Fisik dan Yuridis Pertanahan di Kantor Notaris/PPAT Kabupaten Jember - Firmansyah, Mohammad; Ilyatul Afifah; Laila Kamali (Lembaga Pengembangan Kinerja Dosen, 2026)
The synchronization of physical and juridical land data is a fundamental prerequisite for ensuring legal certainty in every land rights transfer process. Discrepancies between physical field conditions and juridical documents frequently trigger land disputes that impede the performance of Notary/PPAT offices. This community service article reports on a Field Practice (PPL) activity conducted at the Office of Notary/PPAT in Jember Regency during January–February 2026. The primary objective was to provide technical assistance in accelerating physical-juridical data synchronization to guarantee the validity of issued deeds. The method employed was participatory observation, in which students were directly engaged in the partner's workflow. Assistance activities covered document inspection, file digitization, coordination with BPN and tax authorities, and factual field verification. Results indicate that PPL student assistance measurably accelerated the office's administrative workflow, enhanced data validation accuracy, and confirmed conformity between the physical condition of rice-field land and the certificate documents.